Contrasting sediment and water chemistry indicates the extent of the hyporheic zone in a polluted river system - Ciszewski, Dariusz; Aleksander-Kwaterczak, Urszula (Geology, Geophysics and Environment, 2016)
The concentrations of zinc and cadmium were determined in the sediment cores sampled from the floodplain and the channel in the middle reach of the Biała Przemsza River valley (southern Poland). The results were compared to the river water and groundwater chemistry in order to reveal the average extent of the hyporheic flow. The loss of river waters through the river bed due to the natural migration modified by the drainage of the lead-zinc ore mine caused the strong pollution of the river bed sediments with heavy metals to the depth of almost three meters below the water table in the river. Moreover, the similar groundwater and river water chemistry at that depth suggests that the vertical extent of the hyporheic zone, which exceeds a depth of several meters below the channel, can be affected by the drainage of river waters by the lead-zinc mine. The lateral extent of the hyporheic flow, indicated by changes in groundwater chemistry and elevated heavy metal concentrations in the sediments, was of the order of dozen of meters. The investigation documents the large impact of the secondary in situ enrichment of sediments with heavy metals in the hyporheic zone.